EXTENDING THE LIFE TIME OF POLYMER INCLUSION MEMBRANE CONTAINING COPOLY(EUGENOL-DVB) AS CARRIER FOR PHENOL TRANSPORT - Agung Abadi Kiswandono; Dwi Siswanta; Nurul Hidayat Aprilita; Sri Juari Santosa; Takashi Hayashita (Indonesian Journal of Chemistry, 2013)
A study of phenol transport was conducted in correlation to the evaluation of copoly(eugenol-divinylbenzene, DVB) as carrier using polymer inclusion membrane (PIM) method. The performance of copoly(eugenol-DVB) was observed based on the parameters of Membrane Liquid (ML) loss. Some variations, including the effect of plasticizer concentration, stirring speed, and measurement of lifetime of the membrane, were studied. Related to the lifetime, the effect of the concentration of NaNO3 salt was also studied. The tensile strength of membrane before and after the transport was measured and their morphology was characterized using SEM (Scanning Electron Microscope). Results of the study indicate that the value of the tensile strength of the membrane after the transport was lower than that before the transport. The lifetime of the membrane was not only depending on the capacity of the membrane in restraining ML loss, but also on the concentration of salt that was added to the solution of source phase. In addition, the lifetime of the membrane had correlation to the number of ML loss, i.e. the addition of salt lead to lower amount of ML loss and gave longer lifetime. With the addition of 0.1 M NaNO3, the lifetime of the membrane extended to 62 days, which is longer than the lifetime without the addition of NaO3 which was only 7 days.